Sociodemographic and Lifestyle Factors Associated with Undiagnosed Diabetes in Indonesia: Findings from the Basic Health Research Work of Riskesdas 2018 - Ferdina, Ayunina Rizky; Juhairiyah; Yuana, Windy Tri; Setyawati, Budi; Pangestika, Dhita Elsha (Journal of the ASEAN Federation of Endocrine Societies, 2025)
Background. As a developing nation, there has been an increasing trend in non-communicable diseases, including diabetes mellitus (DM) in Indonesia. However, a remarkable proportion of DM cases in this archipelagic country is likely undiagnosed. Objective. This study assessed the sociodemographic and lifestyle factors related to undiagnosed DM in Indonesians. Methodology. This cross-sectional study analyzed secondary data from the 2018 Indonesian Basic Health Research (Riskesdas). It involved 3,755 study subjects, 3,619 individuals with high blood glucose levels meeting and 136 individuals with controlled DM. Multivariable regression analysis examined the associations between sociodemographic and lifestyle factors and undiagnosed diabetes. Result. The study revealed that 80% of the DM cases among the subjects were undiagnosed. Multivariable analysis confirmed that age group, area of residence, employment, wealth quintiles and physical activity were significantly associated with higher odds of undiagnosed diabetes. Notably, sex, smoking status and vegetable consumption did not show any association with the diagnosis status of diabetes. Conclusion. A significant portion of DM cases in Indonesia remain undiagnosed, especially among young adults, rural residents, agricultural workers and lower socioeconomic groups. Improved healthcare access, targeted screening and enhanced health education are essential to ensure early diagnosis and effective management of diabetes.